2023
DOI: 10.1021/acs.chemmater.2c02914
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Calculation Guided High-Purity Layer Control of 4 in. MoS2 by Plasma RIE

Abstract: Two-dimensional molybdenum disulfide (MoS2) is one of the most promising candidates for next-generation semiconductors. Among the advantages offered by MoS2, a tunable bandgap that depends on the thickness is essential for the on-demand manufacturing of nanoelectronics. For this reason, elaborate layer control of MoS2 has been a long-standing research objective. However, prior efforts had several critical issues including surface roughness, poor uniformity/scalability, and impurities. Through this study, we ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…The etching of MoS 2 films was carried out using an Ar + CF 4 + O 2 gas mixture, with the gas mixing ratio and chamber conditions precisely controlled to establish optimal etching conditions. Specific details about MoS 2 etching can be found in previous studies [7,17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The etching of MoS 2 films was carried out using an Ar + CF 4 + O 2 gas mixture, with the gas mixing ratio and chamber conditions precisely controlled to establish optimal etching conditions. Specific details about MoS 2 etching can be found in previous studies [7,17].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, numerical analysis offers the ability to evaluate the impact of different process conditions on the final device performance, aiding in the design and development of advanced semiconductor devices. As a result, the integration of numerical analysis and simulation techniques into the investigation of etching processes facilitates process control and accelerates technology innovation [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…274,620 Recent studies have revealed that a combination of Ar + CF 4 + O 2 plasma gases in an ICP-RIE process can effectively minimize the presence of F residue and maintain the original conductivity of MoS 2 while enhancing the etching peel-off ability. 640 Such a method is capable of achieving a remarkable thickness reduction from bulk (4L) down to a monolayer with high uniformity and a precise layer-by-layer control on a 4-in. 640 Atomic layer etching (ALE) is an alternative process that can be used to precisely control the number of TMD layers without introducing damages or contaminations.…”
Section: Etchingmentioning
confidence: 99%
“…640 Such a method is capable of achieving a remarkable thickness reduction from bulk (4L) down to a monolayer with high uniformity and a precise layer-by-layer control on a 4-in. 640 Atomic layer etching (ALE) is an alternative process that can be used to precisely control the number of TMD layers without introducing damages or contaminations. The process consists of two steps including (i) radical-adsorption (e.g., •Cl) and (ii) reacted-compound desorption by employing a lowenergy Ar plasma.…”
Section: Etchingmentioning
confidence: 99%
See 1 more Smart Citation